A novel nanoscratch device compatible with commercial microscope for in situ tests of materials' mechanics. (26th April 2016) - Li, Ning; Zhao, Hongwei; Zhang, Peng; Shi, Yue; Liu, Yanchao; Jin, Mingjun; Wang, Hui; Dong, Shan
For exploring the mechanical properties and behaviors of new materials, a novel in situ nanoscratch device compatible with commercial microscope has been developed. The developed device with specific dimensions of 178 mm × 165 mm × 78 mm includes the coarse positioning module, the precise feed module, the measurement module, and the control module. Integrating the servo motor, worm and gears, ball screw, flexure hinge, and piezoelectric actuator, the device can realize macroscopical coarse positioning motion and precise feed motion. A novel arrangement of load sensor and indenter with no middle chain is used to reduce the measurement error. Closed-loop control system is established to guarantee the accuracy of load and displacement control. Mechanical properties of the developed device have been proved by calibrating the load sensor, finite element analysis of flexure hinge, and verifying the output performance. The in situ nanoscratch test has been conducted on the single crystal copper. The captured images and finite element analysis prove the feasibility and accuracy of the developed device.